Pillars for a viable Caribbean Community. - CARRINGTON, Edwin W. (1992)
Identifies principles which would form the basis of a viable economic, social and cultural Community. Includes: increased capacity for effective decision-making and implementation at the Community level; more widespread application of the majority decision-making principle; respect for principles of democratic governance and human rights in the constitutional arrangements of member states; institutionalisation of operational mechanisms for broad-based Community consultations; promotion of measures to achieve and maintain internationally competitive economies; pursuit of policies to ensure a Community effectively organised internally with prudent and growing regional and other external linkages; and, the existence and operation of a mechanism of assured financing of Community institutions.